PERMANENT CO₂ STORAGE THROUGH BASALT MINERALISATION IN INDONESIA: A STUDY OF ANGUS ROCK AND MARITIME CCS INTEGRATION - Fieranda Firdaus Azhar Azhar; Edi Kurniawan; Prihastono Prihastono; Hadi Setiawan; I Made Deva Suryawan (Institut Teknologi Sepuluh Nopember, 2026)
Batu Angus in Ternate, composed of Ca- and Mg-rich andesitic basalt, presents a unique opportunity for mineralization-based Carbon Capture and Storage (CCS). Its highly reactive volcanic rock, direct port access, and proximity to the 30 MW Kastela gas plant create ideal conditions for large-scale CO₂ sequestration. This study proposes injecting CO₂-saturated brine into deep basaltic-andesitic reservoirs, where CO₂ reacts with minerals to form stable carbonates. Laboratory simulations at 100°C show rapid Ca²⁺ release and >95% carbonate formation within two years. Reactive transport modeling estimates a conservative storage capacity of 200,000 tCO₂/year and an optimistic scenario exceeding 1 Mt/year, which could offset 80% of regional emissions. Strategically located along Indonesia’s eastern maritime route, Batu Angus can leverage port infrastructure for ship-based CO₂ imports. The project aligns with Indonesia’s CCS regulation (PR14/2024) and Pertamina’s 600 Gt storage potential, positioning Indonesia as a global leader in carbon removal.